Phenotypic variation and genetic alteration of Spathoglottis plicata resulted from in vitro cultured seed irradiated with X-Ray - SUYITNO ALOYSIUS; AZIZ PURWANTORO; KUMALA DEWI; ENDANG SEMIARTI (Society for Indonesian Biodiversity, 2018)
Aloysius S, Purwantoro A, Dewi K, Semiarti E.. 2018. Phenotypic variation and genetic alteration of Spathoglottis plicata resulted from in vitro cultured seed irradiated with X-Ray. Biodiversitas 19: 1642-1648. A terrestrial orchid species among genus Spathoglottis as widely cultivated is S. plicata. Variability development of the species through mutation induction has been carried out, but its morphological variations and genetic changes have not been investigated. The purpose of this study is to identify the phenotypic variation and genetic alteration of S. plicata resulted from in vitro cultured seed irradiated with X-ray. Radiation was given at the doses of 0; 6; 12; 18 and 24 rad. The samples were surviving plants resulted from irradiated seeds. Phenotypic variations observed were the number, length and width of the leaf, number of tiller, and flower characteristics. Genetic alteration was detected from DNA homologous POH1, a key gene determining of shoot morphogenesis. Results show that there are variations of leaf color, length and width of the leaf, and the number of the tiller. Plants start to flower at the age of 30 months. The plants flowering reach 64.7% (WT), 50.0% (6 rad), 33.3% (12 rad), 33.3% (18 rad), and 40% (24 rad). Flower color is ranged from white, white slightly purple, purplish white, light purple, reddish purple and purple, found both in mutants and wild-type groups. The alignment result of POH1 homologous DNA obtained from PCR cDNA shows the nucleotide differences at some points between mutants and wild-type that indicate the occurrence of DNA alteration. X-ray induces the changes of POH1 homologous DNA, but it has no obvious relationship to the flower variation.